Fiscal decentralization, economic growth, and human development: Empirical evidence - Nguyen Thanh Hung; Su Dinh Thanh (Cogent Economics & Finance, 2022)
The objective of this paper is to examine the simultaneous relationship between fiscal decentralization, economic growth, and human development using the panel data of 18 countries over the 2011-2017 period. 3SLS-GMM (Three Stage Least Squares-Generalized Method of Moments Estimator) and GMM-HAC (Generalized Method of Moments-Heteroskedastic and Autocorrelation Consistent estimator) are employed to obtain unbiased coefficients in the system of equation. The results indicate that the significant relationship does exist between fiscal decentralization, economic growth, and human development from different directions. Specifically, economic growth and human development are positively and negatively affected by fiscal decentralization, respectively. These results hold true with alternative estimation methods and sub-indexes of decentralization. Interestingly, economic growth is fostered by human development index, as justified by the statistical evidence of the studied sample, but these results are found to be consistent as well when it comes to expenditure-based decentralization. However, in the opposite direction, the impact of human development on economic growth is ambiguous and only remains significant in the case of expenditure decentralization purposefully utilized as an explanatory variable. Thirdly, economic growth does not give rise to the efficiency of fiscal decentralization, yet could reduce human development instead. The results provide several plausible implications to policy makers.
Keywords: 330; Fiscal decentralization; income inequality; economic growth; GMM-HAC; 3SLSGMM